KESEPADANAN STRUKTUR KALIMAT PADA ARTIKEL KRIMINAL RADAR PEKALONGAN - Mochammad Chamdi Rochmat; Riska Yuliyanti (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2017)
Equivalence structure is a balance between ideas or thoughts and structure of the language used, the proportionality of mind shown by the integrity and coherence of idea or ideas on that sentence, while the equivalence structure shown by the clarity of the presence of subject and predicate, not the subject of a double, the absence of conjunctions intrakalimat used in a single sentence, and the absence of the word "yang" in front of the title. Data used in the form of a fragment of a sentence in a criminal article Radar. Data collection was performed using read and note. Data analysis technique used is the method deskriptif. Equivalence study result sentence structure errors in criminal Radar Pekalongan articles covering subjects resulting vagueness there is a preposition in front of the subject, there is a double subject, conjunctive intrakalimat used in a single sentence, and predicate sentence preceded by the word "yang".